Prognostic impact of coronary microvascular dysfunction assessed by caIMR in overweight with chronic coronary syndrome patients - Feng, Cailin; Abdu, Fuad A.; Mohammed, Abdul-Quddus; Zhang, Wen; Liu, Lu; Yin, Guoqing; Feng, Yundi; Mohammed, Ayman A.; Mareai, Redhwan M.; Lv, Xian; Shi, Tingting; Xu, Yawei; et al. (Frontiers in Endocrinology, 2022)
Objective: Coronary microvascular dysfunction (CMD) may associate with adverse cardiovascular events in obese patients. Coronary angiography-derived index of microcirculatory resistance (caIMR) is proposed as a less-invasive and pressure-wire-free index to assess CMD. We aimed to investigate the impact of coronary microvascular function assessed by caIMR in patients with overweight and chronic coronary syndrome (CCS). Methods: CCS patients who underwent coronary angiography between 2015 to 2018 were included. Overweight was defined as BMI≥24.0kg/m². Impaired coronary microvascular function was defined as caIMR≥25U. The patients were classified according to BMI and caIMR. The primary endpoint was major adverse cardiac events (MACE). Kaplan-Meier and Cox regression analyses evaluated the association between caIMR and MACE. Results: Two hundred and eighty-two CCS patients were enrolled. Among these, 169 (59.93%) were overweight. Impaired coronary microvascular function was higher in overweight patients than in patients with normal weight (49.70% vs. 38.05%; P=0.035). During 35 months of follow-up, 33 MACE had occurred. Among the total CCS population, MACE was higher in patients with high caIMR than in low caIMR (18.11% vs. 6.45%, P=0.003). In subgroups analysis, MACE was higher in overweight patients with high caIMR than low caIMR (20.24% vs. 7.06%, P=0.014), while there were no significant differences in normal-weight patients. Multivariate Cox analysis demonstrated that caIMR≥25 was independently associated with MACE in overweight patients (HR, 2.87; 95% CI, 1.12-7.30; P=0.027) but not in the normal-weight patients. In addition, caIMR showed a significant predictive value for adverse outcomes in overweight patients and provided an incremental prediction when added to a prediction model with BMI. Conclusions: Impaired coronary microvascular function assessed by caIMR was common and is an independent predictor of MACE in overweight patients with CCS.